2006
DOI: 10.1016/j.ijid.2005.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis in Portugal: a retrospective study of eighteen years

Abstract: Seropositivity was associated with both anicteric and icteric leptospirosis. Several risk factors and a higher transmission risk in certain areas were emphasized. Leptospirosis was confirmed as a steadily increasing public health problem; good surveillance, communication, and laboratory support are thus necessary to reduce the impact of leptospirosis in areas at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 23 publications
10
40
0
3
Order By: Relevance
“…The data showed that males and farmers were the most affected by this pathogen. These results are in accordance with the study developed by Vieira et al [5] and Esteves et al [6], where a significant link to professional activities and/or contact with rodents and domestic animals (natural reservoirs for leptospires) was observed.…”
Section: Molecular Diagnosis Of Leptospirosissupporting
confidence: 93%
See 3 more Smart Citations
“…The data showed that males and farmers were the most affected by this pathogen. These results are in accordance with the study developed by Vieira et al [5] and Esteves et al [6], where a significant link to professional activities and/or contact with rodents and domestic animals (natural reservoirs for leptospires) was observed.…”
Section: Molecular Diagnosis Of Leptospirosissupporting
confidence: 93%
“…transmission, such as high levels of humidity (77.0% average/year) and precipitation. In fact, this same trend was previously observed by Vieira et al [5].…”
Section: Molecular Diagnosis Of Leptospirosissupporting
confidence: 90%
See 2 more Smart Citations
“…There is a lack of awareness of leptospirosis mainly due to the subclinical nature of the disease and the technically demanding laboratory tests as MAT, making the disease difficult to diagnose both in the clinic and in the laboratory (WHO 2001, Hartskeerl 2003, Vieira et al 2006). These issues contribute to the process: under-diagnosis, under-reporting and neglection of the disease (Hartskeerl et al 2011).…”
Section: Diagnostic Utility Of An Immunochromatography Test For the Dmentioning
confidence: 99%